Essentials of health policy and law - Wilensky, Sara E.; Teitelbaum, Joel Bern (Jones & Bartlett Learning, 2023)
"Essentials of Health Policy and Law, Fifth Edition provides students of public health, medicine, nursing, public policy, and health administration with an introduction to a broad range of seminal issues in U.S. health policy and law, analytic frameworks for studying these complex issues, and an understanding of the ways in which health policies and laws are formulated, implemented, and applied. Thoroughly revised, the Fifth Edition explores the key health policy and legal changes brought about by the Biden Administration and the presently Democrat-controlled Congress. It also addresses the Covid-19 pandemic, and its many devastating and intertwined health, economic, and social consequences.KEY FEATURES:- New chapters provide an overview of Public Health and explain emergency preparedness.- Updated figures, tables, statistics, and discussion questions- New textbox icons identify discussion questions, special topics and, technical spotlights to help faculty pick and choose the appropriate content- New concluding chapter on Health Advocacy teaches readers the art and skill of advocacy.- Interactive timeline fully updated and incorporated into the eBook"--